Dítě na plátně minulosti : tři poznámky k protektorátní historické próze pro mládež - Ester Nováková (Bohemica Litteraria, 2021)
The study focuses on historical fiction for children and young people written during the Protectorate period. It is based on an analysis of nine representative publications of the genre (by Jaroslav Janouch, Leontina Mašínová, Vladimír Drnák, Marie Holková, Eduard Štorch, Josef Prchal, Vladimír Donát and Václav Fryček), answering three key questions: how the child and childhood are depicted in the mentioned texts, how history is conceived in them and to what extent periodic updates are reflected.